Graffiti, Street Art and Public Space Regulation - Ana Gariso (European Journal of Creative Practices in Cities and Landscapes)
With this work I intend to reflect on the ambivalence that contemporary cities experience in relation to the practices of graffiti and street art: if, on the one hand, we see more works being validated and even promoted by the regulatory agents of urban space, in a strategy of valuing creativity as an intangible asset, there is at the same time a set of strategies to eliminate or prevent the emergence of graffiti or unauthorized street art. This ambivalence stems from the ability these practices have to create new images of the city and new discourses about the public space. I will start from the urban communication studies framework, move towards the discussion that arises from laws and rules that regulate the production of graffiti and street art and then observe the legal framing around these practices in Lisbon and Bologna.